2021
DOI: 10.1177/00033197211040375
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Following Percutaneous Coronary Intervention for Acute Coronary Syndrome: Incidence, Aetiology, Risk Factors and Outcomes

Abstract: We investigated the predictors, aetiology and long-term outcomes of acute kidney injury (AKI) following urgent percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS). Acute kidney injury occurred in 198 (7.2%) of 2917 patients: 14.1% of AKI cases were attributed to cardiogenic shock and 5.1% were classified as atheroembolic renal disease (AERD). Significant risk factors for AKI included age (odds ratio [OR] 1.05, 95% confidence limits [CI] 1.03-1.06), diabetes (OR 1.73, 95% CI 1.20-2.47), h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…The significantly increased mortality rates among patients with AKI versus patients without in the setting of ACS and following PCI are consistent with previous reports [5][6][7][8][9][10][11]25,37,38]. However, the mortality rates among ACS patients who developed AKI in our study are somewhat higher than those reported in most previous studies (up to 44%).…”
Section: Discussionsupporting
confidence: 90%
“…The significantly increased mortality rates among patients with AKI versus patients without in the setting of ACS and following PCI are consistent with previous reports [5][6][7][8][9][10][11]25,37,38]. However, the mortality rates among ACS patients who developed AKI in our study are somewhat higher than those reported in most previous studies (up to 44%).…”
Section: Discussionsupporting
confidence: 90%
“…Similar to others, we confirmed classical risk factors for AKI, such as diabetes mellitus, BMI and preexisting chronic kidney disease [ 21 23 ]. Moreover, the longer duration of ICU stay, and the less common use of steroids and volume expanders in the donor AKI group emphasize the importance of the systemic inflammatory response and intravascular volume depletion respectively as modifiable risk factors for AKI in the ICU setting [ 24 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Their analysis showed that AKI occurred in 14% of the patients who were eligible. Given recent clinical studies from other developed nations have reported the AKI incidence in AMI patients ranged from 7% to 17%, the incidence of AKI in Japanese patients with ACS appears to be similar to that of other countries (3 6).…”
Section: Epidemiology Of Akimentioning
confidence: 55%
“…Given that recent clinical studies from other developed nations have reported that the AKI incidence in AMI patients ranged from 7% to 17%, the incidence of AKI in Japanese ACS patients appears to be similar to that of other countries. [3][4][5][6] Meanwhile, Fujii conducted a multicenter prospective cohort trial (n=2,421) to explore the AKI epidemiology in a mixed Japanese ICU. 7 Their analysis showed that the cumulative incidence of AKI was 44.7% among Japanese ICU patients.…”
Section: Ikemura Et Al Also Analyzed the Clinical Prognosis Of Non-st...mentioning
confidence: 99%